The high frequency surface discharge behaviours of modified polyimide films: the effects of phenyl thioether in the backbone. (24th May 2019) - Huang, Xuwei; Li, Qingmin; Ding, Zi'an; Liu, Tao; Wang, Jian; Wang, Zhongdong
Abstract: High frequency surface discharge is one of the main causes of insulation failure in the high frequency power transformer. In order to extend the endurance lifetime and investigate the behaviours of surface discharge, a series of polyimide films containing phenyl thioether groups were prepared and tested in a self-built experimental platform with a high frequency voltage source. First, the surface discharge inception voltages on the films were tested under high frequency sinusoidal voltage. Then, with the application of continuous high frequency voltage, surface discharge tests were conducted to observe the entire evolution process of surface discharge including its initiation, self-sustaining, streamer and the ultimate flashover. Combining with the frequency-domain dielectric spectra and x-ray diffraction tests, effects of phenyl thioether content on the evolution process in each stage were analyzed. Experimental results and analyses indicate that the discharge inception voltage is opposite to the dielectric loss factor. The depth and distribution of traps caused by crystal and amorphous regions play the different role in various stages of surface discharge. The endurance lifetime of polyimide film containing 40% phenyl thioether was the longest and the effects of which were further discussed based on the discharge behaviour analysis. The paper demonstrates that molecular-structure modification is an effective method to improve the high frequency electrical performance of polyimide.